Der Bruch der Theorie in der Praxis durch Not. Bemerkungen zu Lujo Brentanos Sicht von Arbeitsmarktproblemen - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
– Some Remarks on Lujo Brentano's View of Labor Market Problems Lujo Brentano (1844-1931) aimed for "realism" in economics. Regarding labor market theory, two topics are of particular interest: His investigations on "Hours and Wages in Relation to Production" (Scribner's 1894) and his analysis "On the History and Development of Gilds and the Origins of Trade Unions" (Trubner 1870). The topics of are discussed with a view on recent developments in labor economics.
urn:nbn:de:bvb:19-epub-568-5
Keywords: J3; B1; J1; 330; collective wage setting; efficiency wages; union formation; local culture; organizational failures; fertility; realism; kollektive Lohnsetzung; Gewerkschaft; lokale Kultur; Fertilität; Realismus in der Ökonomik